A Rare Collision Tumor Composed of Follicular Lymphoma and Adenocarcinoma in the Ampulla of Vater: A Case Report - Shioto Suzuki; Fumihiko Tanioka; Keisuke Inaba; Shingo Takatori; Hideto Ochiai; Shohachi Suzuki (Case Reports in Pathology)
The duodenum is infrequently affected by malignant lymphoma, and follicular lymphomas of the duodenum are rare histological subtypes. There are no reported cases of collision of follicular lymphoma and other tumors in the ampulla of Vater. A 57-year-old Japanese man presented with jaundice, and abdominal computed tomography revealed a tumor of the ampulla of Vater invading the pancreatic head with biliary dilatation and a thickened duodenal wall. The patient underwent subtotal stomach-preserving pancreaticoduodenectomy. Histopathology of the resected specimen revealed lymphoid follicular formations with small-to-medium-sized centrocyte-like cells and some centroblast-like cells. The atypical lymphoid cells were immunohistochemically positive for CD10, CD20, and CD79a but negative for CD5 and cyclin D1. BCL2 protein was highly expressed in the follicle centers. The diagnosis was duodenal follicular lymphoma, Grade 1. The follicular lymphoma, 40 mm in diameter, involved duodenal submucosa and regional lymph nodes without distant metastasis. This duodenal follicular lymphoma was partially overlapped by adenocarcinoma of the ampulla of Vater, measuring 25×20 mm, which involved the lower common bile duct, pancreas, and duodenum. We report the first case of a surgically treated collision tumor composed of a rare mass-forming follicular lymphoma and adenocarcinoma of the ampulla of Vater.